NN-TOPSIS strategy for MADM in neutrosophic number setting - Kalyan Mondal; Surapati Pramanik; Bibhas C. Giri (Neutrosophic Sets and Systems, 2021)
Selecting an appropriate alternative among the feasible selection options is a difficult activity for decision makers. Because of the imprecise information and the complexity of decision problem, it is not easy to evaluate the attributes in terms of crisp numbers. To deal with the problem, neutrosophic numbers can be used during the decision process. Neutrosophic numbers can easily describe cognitive information. In this paper, we use neutrosophic numbers to state evaluation information. We define unit neutrosophic number as an effective tool to express cognitive information. We propose novel NN-TOPSIS strategy in neutrosophic number environment. Moreover, we define Euclidean distance in neutrosophic numbers environment, and propose a tangent function to determine unknown attribute weights. We propose linguistic variables in neutrosophic number environment. We present a numerical example dealing with a decision-making problem based on the proposed NN-TOPSIS strategy We present a sensitivity analysis for reflecting the influence of indeterminacy values.We then conduct a comparison analysis between the proposed NN-TOPSIS and other existing decision- making strategies.